Guidelines on the Diagnosis and Treatment of Hypertrophic Cardiomyopathy – 2024 - Fernandes, Fabio (2024)
Hypertrophic cardiomyopathy (HCM) is a form of genetically caused heart muscle disease, characterized by the thickening of the ventricular walls. Diagnosis requires detection through imaging methods (Echocardiogram or Cardiac Magnetic Resonance) showing any segment of the left ventricular wall with a thickness > 15 mm, without any other probable cause. Genetic analysis allows the identification of mutations in genes encoding different structures of the sarcomere responsible for the development of HCM in about 60% of cases, enabling screening of family members and genetic counseling, as an important part of patient and family management. Several concepts about HCM have recently been reviewed, including its prevalence of 1 in 250 individuals, hence not a rare but rather underdiagnosed disease. The vast majority of patients are asymptomatic. In symptomatic cases, obstruction of the left ventricular outflow tract (LVOT) is the primary disorder responsible for symptoms, and its presence should be investigated in all cases. In those where resting echocardiogram or Valsalva maneuver does not detect significant intraventricular gradient (> 30 mmHg), they should undergo stress echocardiography to detect LVOT obstruction. Patients with limiting symptoms and severe LVOT obstruction, refractory to beta-blockers and verapamil, should receive septal reduction therapies or use new drugs inhibiting cardiac myosin. Finally, appropriately identified patients at increased risk of sudden death may receive prophylactic measure with implantable cardioverter-defibrillator (ICD) implantation.